Improvement of endothelial function by pitavastatin: a meta-analysis. (11th February 2018) - Katsiki, Niki; Reiner, Željko; Tedeschi Reiner, Eugenia; Al-Rasadi, Khalid; Pirro, Matteo; Mikhailidis, Dimitri P.; Sahebkar, Amirhossein
ABSTRACT: Objective . Dyslipidemia is commonly associated with endothelial dysfunction and increased cardiovascular risk. Pitavastatin has been shown to reduce total and low-density lipoprotein cholesterol, to increase high-density lipoprotein (HDL)-cholesterol and improve HDL function. Furthermore, several trials explored its effects on flow-mediated dilation (FMD), as an index of endothelial function. The authors evaluated the effect of pitavastatin therapy on FMD. Methods . The authors performed a systematic review and meta-analysis of all clinical trials exploring the impact of pitavastatin on FMD. The search included PubMed-Medline, Scopus, ISI Web of Knowledge and Google Scholar databases. Quantitative data synthesis was performed using a random-effects model, with weighted mean difference (WMD) and 95% confidence interval (CI) as summary statistics. Results . Six eligible studies comprising 7 treatment arms were selected for this meta-analysis. Overall, WMD was significant for the effect of pitavastatin on FMD (2.45%, 95% CI: 1.31, 3.60, p  < 0.001) and the effect size was robust in the leave-one-out sensitivity analysis. Conclusion . This meta-analysis of all available clinical trials revealed a significant increase of FMD induced by pitavastatin.